The performance of cylindrical solar still with hemispherical dome using circular fins in basin - Shahzanan Falah; Dhafer Manea Hachim; Wisam A. Abd Al-wahid (International Journal of Thermofluids)
As freshwater becomes depleted in many regions around the world and the need to use brackish water increases, the importance of solar resources (which are environmentally sustainable and economically viable) continues to increase. This study was designed to assess the efficiency of a modified cylindrical solar still which was outfitted with a hemispherical dome and fins. The evaluation was conducted theoretically and experimentally in Najaf, Iraq (at the geographical coordinates of 31.590°N and 44.190°E). The research methodology involved the numerical testing of seven proposed models and the identification of the optimal variables for the solar still's performance. This study conducted experimental tests on the best-performing models from the numerical simulation. During these tests, the daily production of distilled water from the still ranged from 2.72 to 3.7 kg/m². The experimental results closely correlate with the results obtained from the numerical simulations of a stagnant system (with and without fins). In the numerical simulation study, the results demonstrated that the addition of fins to the solar still increases the surface area of the tank which resulted in a peak throughput of 11.853 kg/m². The highest total productivity achieved for January, March, July, and October are 3.011 kg/m², 7.686 kg/m², 11.853 kg/m², and 4.279 kg/m², respectively. The results demonstrated a significant improvement in the efficiency of the distillation device which exceeded 64.7 % when compared to the finless model. The finned model has the advantage of increased productivity and ease of manufacture. The most efficient arrangement and cumulative productivity of this improvement was achieved via the use of five fins (each of which measures 8 mm in height) arranged at a fixed height in the cylinder.